Small-Scale Farmers’ Decision-Making for Crop Selection and Production Practices in Northern Haiti - Priscilla Zelaya; Amy Harder; Grady T. Roberts (Journal of International Agricultural and Extension Education, 2017)
Decision-making is an essential aspect of farming. The decisions farmers make affect their overall yield and, ultimately, impact their livelihoods. Understanding the different factors impacting farmer decision-making can provide insight for extension providers to improve the quality of service. In Haiti, the vast majority of farms are smallholder farms averaging less than 1.5 hectares (Ministry of Agriculture, Natural Resources, and Rural Development [MARNDR], 2010). The purpose of this study was to determine the decision-making practices of small-scale farmers in Northern Haiti related to crop production. The following research objectives guided the study: (a) identify the factors associated with crop selection, and (b) identify reasons farmers engage in specific practices for crop production. Results from this study found that small-scale farmers in the North Department reported using the following factors to determine crop selection: financial security, familial traditions, concern for family, and availability of financial resources. When determining practices for crop production, farmers relied on the following drivers: financial limitations and previous learning experiences. Recommendations include increasing the availability of resources to the farmers in this region in order to create a solid foundation for behavior adoption and increased farmer capabilities.
Keywords: Haiti; Food Security; Small-Scale; Farmers; Decision-Making